2022
DOI: 10.1136/thorax-2022-219052
|View full text |Cite
|
Sign up to set email alerts
|

Single dose of budesonide/formoterol turbuhaler compared to salbutamol pMDI for speed of bronchodilator onset in asthma: a randomised cross-over trial

Abstract: ObjectiveTo compare bronchodilator response after to salbutamol and budesonide/formoterol in adults with stable asthma.MethodsA double-blind, cross-over, single-centre, placebo-controlled, non-inferiority trial. Adults with stable asthma were randomised to different orders of two treatment regimens: two actuations of placebo via MDI and one actuation of budesonide/formoterol 200/6 µg via turbuhaler; and one actuation of placebo turbuhaler and two actuations of salbutamol 100 µg via MDI. The primary outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…A newly published double-blind, crossover, single-center, placebo-controlled non-inferiority study[ 30 ] compared the bronchodilator response to salbutamol and budesonide/formoterol in adults with stable asthma [ 30 ]. This study found no evidence of non-inferiority against a boundary of a forced expiratory volume in 1 s (FEV 1 ) of − 0.06 L for the difference between budesonide/formoterol 200/6 µg compared with salbutamol 200 µg at the timepoint of 2 min [ 30 ]. There were 33 adverse events reported among 22 participants [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A newly published double-blind, crossover, single-center, placebo-controlled non-inferiority study[ 30 ] compared the bronchodilator response to salbutamol and budesonide/formoterol in adults with stable asthma [ 30 ]. This study found no evidence of non-inferiority against a boundary of a forced expiratory volume in 1 s (FEV 1 ) of − 0.06 L for the difference between budesonide/formoterol 200/6 µg compared with salbutamol 200 µg at the timepoint of 2 min [ 30 ]. There were 33 adverse events reported among 22 participants [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found no evidence of non-inferiority against a boundary of a forced expiratory volume in 1 s (FEV 1 ) of − 0.06 L for the difference between budesonide/formoterol 200/6 µg compared with salbutamol 200 µg at the timepoint of 2 min [ 30 ]. There were 33 adverse events reported among 22 participants [ 30 ]. Only one adverse event (headache) was thought to be related to the administration of salbutamol [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A double-blind randomized controlled trial (RCT) has shown no difference between the bronchodilator effect of salbutamol and ICS-FOR in average forced expiratory volume in 1 s (FEV 1 ) achieved from first dose to a 90-min assessment point [mean ratio 98.4%; 95% confidence interval (CI) 91.6, 105.7; p = 0.66] [ 30 ]. In a different RCT, focusing on an earlier timepoint clinically relevant in terms of acute bronchodilation (2 min), the non-inferiority FEV 1 boundary of − 0.06 L for budesonide (BUD)-FOR compared with salbutamol was not met [ 31 ]; mean FEV 1 change from baseline 2 min after treatment administration was 0.08 L for BUD-FOR [standard deviation (SD) 0.14, n = 49] and 0.17 L for salbutamol (SD 0.18, n = 48) [ 31 ]. Over the 30 min post-dose, FEV 1 was higher with salbutamol than BUD-FOR (mean difference 0.10 L, p < 0.001); however, this was less than the suggested threshold for the minimum patient perceivable improvement of 0.23 L [ 32 ], and the study did not show any differences in perceived breathlessness between the treatments [ 31 ].…”
Section: Saba Pharmacologymentioning
confidence: 99%
“…Symbicort is a long-term maintenance medicine containing budesonide, a corticosteroid, and formoterol, a rapid and long-acting beta2-agonist, used twice daily to treat asthma in adults. The drug functions fifteen minutes after inhalation, providing a rapid, clinically effective bronchodilator response and relieving lung inflammation [ 13 , 14 ]. However, to our knowledge, no previous studies have assessed lung function during serial follow-ups in a predefined period, especially in exploring the medication effects and the correlation with airway measurement metrics.…”
Section: Introductionmentioning
confidence: 99%